Microbottle resonator for temperature sensing - Malathy*, Batumalay; Md Ashadi, Md Johari; Muhammad Imran Mustafa, Abdul Khudus; Mohd Hafiz, Jali; Abdullah, Al Noman; Sulaiman Wadi, Harun (IOP Publishing Ltd, 2019)
The whispering gallery mode on the surface of the microbottle optical resonator (MBR) was studied in this research paper as a relative temperature sensor. The MBR is formed by a technique known as "soften-and-compress" allowed SMF-28 silica fiber to be formed in bottle structure with a bottle diameter Db = 190μm, stem diameter of Ds = 125μm and bottle length of Lb = 182μm. The Q-factor of the MBR is defined by excited with bare microfiber with 2 μm diameter and managed to have >105. The range of temperature between 40°C to 100°C is then employed to the MBR as a temperature sensor for analysis purpose. The performance of the MBR is promising with sensitivity 0.0149 dB/0C with linearity 94% and P-value >105 which is defined as a good sensor. The sensitivity value from the wavelength shift is 1.3 pm/0C. The repeatability and stability of the MBR can be employed as a temperature sensor.